(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Ghimire S, Koju NP. 2021. Short Communication: Fish diversity and its relationship with environmental variables in Kamala River, Nepal. Biodiversitas 22: 4865-4871. Kamala River originates from the lower part of the Mahabharat range and flows through inner to outer Terai, providing a broad range of ecosystem services; provisioning, regulating, supporting, and cultural. However, the information regarding the environmental factors and species diversity in the river is not available enough. Hence the study aimed to explore baseline information on the diversity and abundance of fish and their relation to environmental variables. The fish diversity was assessed in five sections of Kamala River and correlated with different environmental variables. The study was carried out during September- October 2019, marking the post-monsoon season of Nepal. Fish samples were collected using cast nets, and physiochemical parameters were analysed onsite and in the laboratory. Altogether 19 freshwater fish species belonging to 5 orders, 8 families, and 15 genera were recorded. Cyprinids were the most dominant in the river, while Channids, Mastacembelids, Botiids, Sisorids, Gobiids were represented less. The Redundancy Analysis (RDA) ordination method revealed that species variation was correlated with temperature, Electrical Conductivity (EC), Total Dissolved Solids (TDS), and nitrate. Nonetheless, different river sections were disturbed due to mining, deforestation, and construction activities, which could pose a real threat to fish diversity and population, and other aquatic organisms.